How behavioral economics influences management decision-making : a new paradigm - Monahan, Kelly A. (Perspectives in behavioral economics and the economics of behavior., 2018)
How Behavioral Economics Influences Management Decision-Making: A New Paradigm critically reexamines the management function in 21st century workplaces. The book seeks to examine and explain the real-world behaviors of employees and acknowledge the human nature that binds us all together and how to appeal to these characteristics in order to help organizations prosper. It explores well-observed but rarely understood features of employee cognition and irrationality, challenging the dominant discourse and offering an alternative to gain greater competitive advantage in today's complex markets. It also provides an effective new framework on the best ways to develop relevant management skills as they pertain to hiring, performance management, change management, employee engagement, and goal setting. As the knowledge economy continues to grow, the social bonds within companies will prove to be a key differentiation to deliver on the next big idea. Developing productive decisions with staff in the talent-driven global economy increasingly requires the development of "intrinsic" meaning in work, a human-centered work-place culture, and human-focused working practices. This book tackles these topics in comprehensive and efficient detail